2011
DOI: 10.3109/01480545.2010.507207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dipotassium trioxohydroxytetrafluorotriborate (K2[B3O3F4OH]) on genetic material and inhibition of cell division in human cell cultures

Abstract: We have examined antiproliferative, cytotoxic, and genotoxic potential of a halogenated boroxine dipotassium trioxohydroxytetrafluorotriborate (K₂[B₃O₃F₄OH]). The impact on cell growth was evaluated by alamarBlue assay in basal cell carcinoma culture. Cytostatic, cytotoxic, and genotoxic potential were evaluated in lymphocytes culture, applying cytokinesis-block micronucleus cytome assay and chromosome aberrations analysis. Tested concentrations (0.05, 0.1, 0.2, and 0.4 mg/mL) were correlated with inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…2 was used to determine a reaction rate constant k and ln k. This equation comes from the balanced equation of the overall chemical reaction given by Equations (1) and (2). Then, ln k versus 1/t was plotted and a linear regression found to determine the slopes.…”
Section: Determination Of Activation Energymentioning
confidence: 99%
See 1 more Smart Citation
“…2 was used to determine a reaction rate constant k and ln k. This equation comes from the balanced equation of the overall chemical reaction given by Equations (1) and (2). Then, ln k versus 1/t was plotted and a linear regression found to determine the slopes.…”
Section: Determination Of Activation Energymentioning
confidence: 99%
“…It has been suggested that halogenated boroxines can be used in the prevention and/or treatment of benign or malignant changes of the epidermis visible in the form of, for example, nevus or skin cancer. In previous works [2][3][4] , it was shown the effects of dipotassium trioxohydroxytetrafluorotriborate (K 2 [B 3 O 3 F 4 OH]) on genetic material and inhibition of cell division in human cell cultures. Tested concentrations (0.04, 0.1, 0.2 and 0.4 mg mL À1 ) were correlated with inhibition of cell growth in basal cell carcinoma culture and with the lymphocytes proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…This discovered impact on human cells has initiated our research on the effects of this compound on chromosomes, microorganisms, inhibition of enzymes, and proliferation of cancer cells. In previous work 11 it was shown its effects on genetic material and inhibition of cell division in human cell cultures. Tested concentrations (0.04, 0.1, 0.2 and 0.4 mg mL À1 ) were correlated with inhibition of cell growth in basal cell carcinoma culture and with the lymphocytes proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…K 2 (B 3 O 3 F 4 OH) is explored as useful in treatment of benign and malignant skin changes, such as nevus or skin cancer 8,9 . First published effects of its bioactivity, revealed a potential for inhibition of lymphocytes proliferation and cell growth of basal cell carcinoma culture as well as certain clastogenic potential 10 .…”
Section: Introductionmentioning
confidence: 99%